2003
DOI: 10.1097/00005537-200303000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Dog Bites of the Scalp, Face, and Neck in Children

Abstract: The injured child is typically a 5-year-old boy attacked by a familiar dog at home or in the local neighborhood. Children with the diagnosis of attention deficit hyperactivity disorder appear to be at a higher risk of dog bite injuries and should be monitored during interactions with dogs. The goal of surgical management for severely injured children is to avoid immediate mortality and to establish a schedule of multiple-staged procedures for revision surgeries. An optimal cosmetic result is the principal goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 14 publications
4
54
1
8
Order By: Relevance
“…Mitchell et al showed that the attack site was familiar to the child in 59% of cases 2 . Although CDC Injury Center found 25 breeds to be involved in attacks, the pit bull and rottweiler breeds were responsible for 50% of all cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mitchell et al showed that the attack site was familiar to the child in 59% of cases 2 . Although CDC Injury Center found 25 breeds to be involved in attacks, the pit bull and rottweiler breeds were responsible for 50% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al showed that there is poor evidence of benefit, while other authors have suggested using antibiotics in any dog bite injury with bone involvement, especially if there is CSF inoculation 2,3,8,9 . If infection does occur, Pasteurella multocida is isolated in culture in more than 50% of the cases, followed by Staphylococcus (25%) and Streptococcus (15%) 8 .…”
Section: Fig 4 Case 2 (A) Scalp Injuries To Occipital Area (→); (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…The average age of patients in our study agrees with other published reports that focused on injuries of the head and neck. 3,[12][13][14] Younger children are more prone to injuries to the face due to their smaller stature which is on the same level as dogs, their relatively large head size compared with their body, and their lack of understanding and fear of dogs leading them to bring their faces within an intimate and threatening distance from the dog. 3,12 Many authors have reported that males are more likely to suffer a dog bite, 10,12 but like others, 8,15 we found no gender difference.…”
Section: Discussionmentioning
confidence: 99%